A new species of Crinia (Anura: Myobatrachidae) from the Flinders Ranges, South Australia - Donnellan, S.; Anstis, M.; Price, L.; Wheaton, L. (Zootaxa, 2012)
We describe, as a new species, the northern Flinders Ranges populations of the myobatrachid frog Crinia riparia. It isdistinguished from C. riparia sensu stricto on the basis of reciprocal monophyly of mitochondrial genes, absence ofhaplotype sharing in a nuclear gene, fixed differences in allozyme loci and differences in larval oral disc morphologyconsistent with less adaptation to stream habitats. We were not able to reliably distinguish the taxa on the basis of adultmorphology. The geographic range of C. riparia sensu stricto is now reduced to a 75 kilometre section of the southernFlinders Ranges from Napperby Gorge in the south to Mt Brown in the north suggesting that an assessment of its conservation status is warranted.